Eliot midnight superhero - Cottringer, Anne.; Smith, Alex T. (London : Scholastic Children's Books, 2013)
Eliot Jones, an ordinary boy by day, becomes a superhero when the sun goes down, capable of taming lions, recovering the queen's jewels, and maybe even saving the world.
3.7
K-3.
K-3
Keywords: Boys -- Juvenile fiction; Superheroes -- Juvenile fiction; Boys -- Fiction; Superheroes -- Fiction; Boys -- Fiction; Superhoeroes -- Fiction; Picture books for children